Cancer Risk Stratification of Anal Intraepithelial Neoplasia in Human Immunodeficiency Virus–Positive Men by Validated Methylation Markers Associated With Progression to Cancer. (8th April 2020) - van der Zee, Ramon P; Richel, Olivier; van Noesel, Carel J M; Ciocănea-Teodorescu, Iuliana; van Splunter, Annina P; ter Braak, Timo J; Nathan, Mayura; Cuming, Tamzin; Sheaff, Michael; Kreuter, Alexander; Meijer, Chris J L M; Quint, Wim G V; et al.
Abstract: Background: High-grade anal intraepithelial neoplasia (HGAIN; AIN2–3) is highly prevalent in HIV+ men, but only a minority of these lesions progress towards cancer. Currently, cancer progression risk cannot be established; therefore, no consensus exists on whether HGAIN should be treated. This study aimed to validate previously identified host cell DNA methylation markers for detection and cancer risk stratification of HGAIN. Methods: A large independent cross-sectional series of 345 anal cancer, AIN3, AIN2, AIN1, and normal control biopsies of HIV+ men was tested for DNA methylation of 6 genes using quantitative methylation-specific PCR. We determined accuracy for detection of AIN3 and cancer (AIN3+) by univariable and multivariable logistic regression analysis, followed by leave-one-out cross-validation. Methylation levels were assessed in a series of 10 anal cancer cases with preceding HGAIN at similar anatomic locations, and compared with the cross-sectional series. Results: Methylation levels of all genes increased with increasing severity of disease ( P < .05). HGAIN revealed a heterogeneous methylation pattern, with a subset resembling cancer. ZNF582 showed highest accuracy (AUC = 0.88) for AIN3+ detection, slightly improved by addition of ASCL1 and SST (AUC = 0.89), forming a marker panel. In the longitudinal series, HGAIN preceding cancer displayed high methylation levels similar to cancers. Conclusions: We validated the accuracy of 5 methylation markers for the detection of anal (pre-) cancer. High methylation levels in HGAIN were associated with progression to cancer. These markers provide a promising tool to identify HGAIN in need of treatment, preventing overtreatment of HGAIN with a low cancer progression risk. Abstract : Independent validation of host cell DNA methylation markers associated with anal carcinogenesis demonstrates their significant prognostic value for treatment decision making of high-grade anal intraepithelial neoplasia. This is further emphasised by a longitudinal analysis-based association with progression to anal cancer.